Distribution of Mutual Fund Shares—Recent Developments in SEC Regulation (Washington University Law Quarterly, 1975)
This Symposium addresses recent changes in SEC regulation of mutual fund distribution and assess the consequences that may arise from these modifications.
Keywords: Mutual funds; Investment trusts